Parâmetros genéticos para características de prolificidade nas raças Landrace e Large White - Mariana Anrain (2011)
Data from Landrace (LD) and Large White (LW) sows were analyzed to estimate variance components for total number of piglets born (NTN), number of piglets born alive (NV) and number alive at day 5 after birth (NV5). REML mixed model equations included the fixed effects of sow year and birth season, and litter contemporary group (sow conceptionseason-sow order of parity). In addition, univariate analyses included, alternatively, direct genetic, maternal genetic and permanent environmental effects, resulting in four models for each trait and each breed. Multiple trait analysis was performed to estimate geneticcorrelations among the traits. Univariate models comparison indicated that the model containing only direct genetic effect was the most appropriated for parameter estimation. Estimates of heritability for NTN, NV e NV5 were calculated and ranged from .15 for LW and .08 to .12 for LD (NTN), from .14 for LW and .05 to .12 for LD (NV) and from .11 to.12 for LW and .03 to .08 for LD (NV5). Results suggested that selection for NV5 could be an interesting alternative to increase litter size and others components by indirect selection for piglet survival and maternal ability.